Psychological Loneliness and Psychological Security and the Relationship between them among a Sample of Foreign Students at Yarmouk University - Bani Mustafa , Manar; Alshrefen, Ahmad (Jordan Journal of Educational Sciences, 2013)
The study aimed at investigating the level of psychological loneliness and psychological security and the relationship between them among a sample of foreign students at Yarmouk University. The study sample consisted of some available (158) male and female students who were enrolled in the second semester 2011-2012. The results showed an average level of psychological loneliness, and a significant correlation between the two variables, except for the dimension of subjective feelings which was negatively correlated with psychological security and its dimensions. The results also showed statistically significant differences in the level of psychological loneliness and dimensions of family relationships and subjective feelings that were attribute to gender in favor of females. In addition, the study found as well, differences in the level of psychological loneliness attributed to the level of achievement in favor of both excellent and low (satisfactory) achievement. Differences were also found in the level of psychological loneliness, due to the level of achievement in favor of those with excellent and low achievement. Moreover, differences in the level of psychological security and subscales were found due to gender in favor of male students.